Accounting standards convergence dynamics: International evidence from club convergence and clustering. Issue 3 (28th October 2014) - Apergis, Nicholas; Christou, Christina; Hassapis, Christis
Abstract : Purpose: – This paper aims to explore convergence of accounting standards across worldwide adopted measures to investigate whether countries that have not completely adopted International Accounting Standards across the globe have displayed a tendency to act so. Design/methodology/approach: – The new panel convergence methodology, developed by Phillips and Sul (2007), is employed. Findings: – The empirical findings suggest that countries form distinct convergent clubs, albeit on a limited prevalence, yielding support to the notion that on a global basis firms and countries have initiated processes that will eventually lead them to a uniform pattern of employing common accounting standards. Practical implications: – These findings have substantial implications on a firm level, mainly for differences in accounting quality as well as for differences in their cost of capital, thus leading the regulatory authorities to opt for further improvements in financial reporting. Originality/value: – The novelties of this paper first, stem from the fact that it is the first time in the relevant literature that an empirical study attempts to formally measure whether the accounting world exhibits a tendency for accounting standards convergence or whether tactics and policies remain stagnant, acquiring drastic policy measures to speed up the convergence process. In addition, this study employs the implementation of the new methodology of panel convergence testing. This methodology has several appealing characteristics.